Disruption of Tissue-Specific Fucosyltransferase VII, an Enzyme Necessary for Selectin Ligand Synthesis, Suppresses Atherosclerosis in Mice - Gitlin, Jonathan M. (American Society for Investigative Pathology, 2009)
A hallmark feature of atherosclerosis is that circulating mononuclear cells adhere to the endothelium and migrate into the subendothelial space. This adhesion is mediated by molecules such as selectins that are expressed on the surfaces of both leukocytes and endothelial cells. In this study, we have determined the role of tissue-specific fucosyltransferase VII (FucT-VII), an enzyme necessary for selectin ligand synthesis, in the development of atherosclerosis. We adopted a scheme of transplanting either FucT-VII(−/−)GFP(+) bone marrow into lethally irradiated low-density lipoprotein receptor low density lipoprotein receptor mice or FucT-VII(+/+) GFP(+) bone marrow into FucT-VII(−/−), low density lipoprotein receptor double-mutant mice to evaluate the roles of E- and P-selectin ligands versus L-selectin ligands, respectively, in diet-induced atherosclerosis. GFP was used to track the transplanted cells. Our results indicate that, compared with controls, selective disruption of E- and P-selectin ligand synthesis resulted in a significant reduction in atherosclerosis. Selective disruption of L-selectin ligand production did not reduce atherosclerosis as robustly as disruption of E- and P-selectin ligands. In both groups, however, there was a significant reduction in the accumulation of macrophages in the lesion. These studies indicate that selectin ligands, particularly those for E- and P-selectins, play an important role in the pathogenesis of atherosclerosis by regulating macrophage accumulation in atherosclerotic lesions.